Effects of Linear Visual-Vestibular Conflict on Presence, Perceived Scene Stability and Cybersickness in the Oculus Go and Oculus Quest - Kim, Juno; Palmisano, Stephen; Luu, Wilson; Iwasaki, Shinichi (Frontiers in Virtual Reality, 2021)
Humans rely on multiple senses to perceive their self-motion in the real world. For example, a sideways linear head translation can be sensed either by lamellar optic flow of the visual scene projected on the retina of the eye or by stimulation of vestibular hair cell receptors found in the otolith macula of the inner ear. Mismatches in visual and vestibular information can induce cybersickness during head-mounted display (HMD) based virtual reality (VR). In this pilot study, participants were immersed in a virtual environment using two recent consumer-grade HMDs: the Oculus Go (3DOF angular only head tracking) and the Oculus Quest (6DOF angular and linear head tracking). On each trial they generated horizontal linear head oscillations along the interaural axis at a rate of 0.5 Hz. This head movement should generate greater sensory conflict when viewing the virtual environment on the Oculus Go (compared to the Quest) due to the absence of linear tracking. We found that perceived scene instability always increased with the degree of linear visual-vestibular conflict. However, cybersickness was not experienced by 7/14 participants, but was experienced by the remaining participants in at least one of the stereoscopic viewing conditions (six of whom also reported cybersickness in monoscopic viewing conditions). No statistical difference in spatial presence was found across conditions, suggesting that participants could tolerate considerable scene instability while retaining the feeling of being there in the virtual environment. Levels of perceived scene instability, spatial presence and cybersickness were found to be similar between the Oculus Go and the Oculus Quest with linear tracking disabled. The limited effect of linear coupling on cybersickness, compared with its strong effect on perceived scene instability, suggests that perceived scene instability may not always be associated with cybersickness. However, perceived scene instability does appear to provide explanatory power over the cybersickness observed in stereoscopic viewing conditions.